The sixth world food survey - FAO (FAO, 1996)
The paper provides a wealth of data, especially in its Appendix tables which will hopefully assits national governments and international agencies in their joint effort to eliminate food inadequacy and undernutrition so that, one day in the not too distant future, food security may be guaranteed to all men and women everywhere.